2012
DOI: 10.1001/archophthalmol.2012.1043
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Ranibizumab on Diabetic Retinopathy Severity and Progression

Abstract: Intravitreal ranibizumab reduced the risk of DR progression in eyes with diabetic macular edema, and many ranibizumab-treated eyes experienced improvement in DR severity. Because these results are exploratory, the use of intravitreal ranibizumab specifically to reduce DR progression or cause DR regression requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(182 citation statements)
references
References 20 publications
11
168
0
3
Order By: Relevance
“…FDA approved ranibizumab for the treatment of DME in 2012 and for the treatment of DR in February 2015. Evidence for DME treatment with ranibizumab is based on data from phase II and III RTCs, including the Safety and Effi cacy of Ranibizumab in DME (RESOLVE) 55 ; Ranibizumab for Edema of the mAcula in Diabetes (READ-2) 56 ; Core Study to Assess the Effi cacy and Safety of Ranibizumab Intravitreal Injections (RESTORE) 57 ; Diabetic Retinopathy Clinical Research Network (DRCR.net) Protocol I 58 and Study of Ranibizumab Injection in Subjects with CS-DME Secondary to Diabetes (RISE and RIDE) 59 . Afl ibercept (Eylea®; Bayer Healthcare Pharmaceuticals, Berlin, Germany) is a 115-kDA recombinant fusion protein consisting of the VEGF binding domains of human VEGF receptors 1 and 2 fused to the Fc domain of human immunoglobulin-G1 60 .…”
Section: Novel Treatment Options For Dmementioning
confidence: 99%
“…FDA approved ranibizumab for the treatment of DME in 2012 and for the treatment of DR in February 2015. Evidence for DME treatment with ranibizumab is based on data from phase II and III RTCs, including the Safety and Effi cacy of Ranibizumab in DME (RESOLVE) 55 ; Ranibizumab for Edema of the mAcula in Diabetes (READ-2) 56 ; Core Study to Assess the Effi cacy and Safety of Ranibizumab Intravitreal Injections (RESTORE) 57 ; Diabetic Retinopathy Clinical Research Network (DRCR.net) Protocol I 58 and Study of Ranibizumab Injection in Subjects with CS-DME Secondary to Diabetes (RISE and RIDE) 59 . Afl ibercept (Eylea®; Bayer Healthcare Pharmaceuticals, Berlin, Germany) is a 115-kDA recombinant fusion protein consisting of the VEGF binding domains of human VEGF receptors 1 and 2 fused to the Fc domain of human immunoglobulin-G1 60 .…”
Section: Novel Treatment Options For Dmementioning
confidence: 99%
“…These studies showed that high levels of VEGF cause closure of retinal vessels, which for a period of time can be reopened by VEGF suppression, but, without treatment or by suspending treatment, permanent closure and retinal nonperfusion occur. Suppression of VEGF also resulted in improvements in background diabetic retinopathy (36). Thus, VEGF plays a larger role in the pathogenesis of ischemic retinopathies than previously expected, but the mechanism by which it promotes reversible vessel closure is unknown.…”
Section: Introductionmentioning
confidence: 85%
“…For example, the Diabetic Retinopathy Clinical Research Network (DRCRnet) suggests that the average number of injections in the first, second, and third year of treatment for DME was 9, 3, and 2, respectively, to maintain vision gained (17). Exploratory analysis of trial data demonstrated that ranibizumab injections could reduce risk of progression and increase likelihood of regression of diabetic retinopathy severity among patients with DME (19).…”
Section: Efficacymentioning
confidence: 99%